The body as a mirror of inequality in México during the second half of the twentieth century - Moramay Lopez-Alonso (História, Ciências, Saúde: Manguinhos, 2024)
This paper examines how variations in the height and health of Mexicans during the second half of the twentieth century reflect the evolution of economic inequality, as its effects have repercussions on the health and nutritional conditions of the population. The average height of Mexican adults had a modest increase with respect to the possibilities of human plasticity. These anthropometric variations were the result of the incorporation of advances in science and technology leading to improved standards of living among the population. Body changes were impacted by dietary habits, urbanization, and government policies supporting food production and distribution.